Curriculum Considerations for Developing Mathematical Talent in Elementary Students - M. Katherine Gavin (Education Sciences, 2024)
To effectively nurture the talents of elementary students with mathematical talent they need to be challenged with an advanced curriculum that is designed with their specific needs in mind. The purpose of this paper is to describe an effective model for developing such a curriculum and explore effective, research-based examples of curriculum and instruction using this model. The paper begins with a review of literature covering a broadened definition of mathematical talent that showcases the need for a more complex and multi-dimensional curriculum to nurture their talents. Next, evidence-based curriculum considerations for talented students at the elementary level are explored. Essential characteristics of mathematics curriculum for talented students are detailed including a focus on advanced content, conceptual development and higher-level processes akin to those used by mathematicians. Accompanying research-based instructional strategies to increase challenge, complexity, and creativity are outlined. Examples at the primary and elementary grade levels are provided to illustrate effective, research-based curriculum and instruction that develop mathematical talent in advanced students.